Postseismic gravity changes after the 2011 Tohoku earthquake observed by superconducting gravimeters at Mizusawa, Japan - Yoshiaki Tamura; Takahito Kazama; Ryuichi Nishiyama; Koji Matsuo; Yuichi Imanishi (Earth, Planets and Space, 2023)
Abstract Postseismic gravity changes after the 2011 Tohoku earthquake (Mw9.0) were investigated using the data from superconducting gravimeters (SGs) at Mizusawa, Japan. The data in the period from 2014 to 2021 were used in the analysis. The SG data were first corrected for instrumental drift using the results of absolute gravity measurements. Then, correction for the hydrological effect was applied based on physical modeling of soil moisture. Finally, the effect of vertical displacement of the station (free-air effect) was corrected using GNSS data. After these corrections, residual gravity indicated a long-term increase, with its rate gradually decreasing with time. This fact suggests that viscoelastic relaxation after the earthquake played an important role in producing the long-term gravity changes. Fitting a decaying exponential function of time to the residual series yielded 89.4 ± 4.4 µGal (1 µGal = 10–8 ms–2) as the total gravity change and 635 ± 17 days as the characteristic time scale. In addition to the ground-based observations, the data from satellite gravity missions GRACE/GRACE-FO were analyzed to retrieve gravity changes at Mizusawa. Similar analysis of the satellite-based data yielded 15.2 ± 1.6 µGal as the total gravity change and 3444 ± 599 days as the characteristic time scale. The difference in the estimates of the total gravity change, of a factor of about 6, from the ground-based and the satellite-based observations may be attributed to the limited spatial resolution in the latter method. The difference in the estimates of the time scale, of a factor of about 1/5, may originate from the difference in the depth where the two kinds of gravimetry are mainly sensitive. Referring to recent theoretical studies on postseismic deformations after the 2011 Tohoku earthquake, our results can be interpreted consistently by assuming the existence of a layer of viscoelastic materials with viscosity $$2× {10}^{18} \text{Pa s}$$ 2 × 10 18 Pa s underneath the Tohoku area of Japan. Graphical Abstract